Assessing cleaning in remanufacturing: a case study of shot blasting efficiency to alternator design - Noraini Abdul Malek,; Dzuraidah Abd Wahab,; Zambri Harun,; Nurhasyimah Abd Aziz,; Abdul Hadi Azman,; Mohd Radzi Abu Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Cleaning is a crucial step in the remanufacturing of end-of-life components. The main purpose of cleaning is to remove all contaminant items such as dirt, oils, dust in order to facilitate the process of core inspection before moving on to the subsequent step to complete the remanufacturing activity. However, there are issues/challenges related to the cleaning methods that affect the process efficiency. It has also been reported that the cleaning process is time consuming and has adverse impact to the environment. Cleaning is directly influenced by the various cleaning methods and the design features of each core/incoming parts. Therefore, the aim of this paper is to evaluate the effectiveness of shot blasting cleaning method from core design perspectives in the case of an alternator. The results will be assessed based cleanliness level after the cleaning process on the core surface, complex shape, geometry, and joining method. The outcome demonstrates that the complexity of the core design also affects the cleaning process efficiency. According to the study shot blasting cleaning method without any pre-treatment process was insufficient to fully clean the core. Hence, it is suggested that considering certain parameters of the shot blasting medium, such as size, type, and shape variations, can enhance the effectiveness of shot blasting as a cleaning method for used alternators in remanufacturing.